Penerapan Teknologi Solar House Evaporatin Pada Produksi Garam Berkelanjutan - Ruslan; Yusiran; Muhammad Subhan; Ariyansyah; Muhammad Ziaulhaq (Jurnal Pemberdayaan Masyarakat, 2025)
The urgency of implementing the Empowerment of Regional Featured Product Business Partners program in the PUGAR Farmers in Sanolo Village as an effort to increase the quality and quantity of sustainable salt production. The aim of this program is to apply integrated Solar House Evaporation (SHE) technology to sustainable salt production. This activity is carried out through several stages starting with program outreach activities to partners. The next stage is making SHE including preparing tools and materials for making SHE, making SHE frames, installing plastic roofs, installing plastic geomembranes, installing filter pipes. The final stage is salt production which includes preparing raw water/old water, the old water is channeled to the crystallization table at the SHE through a filter pipe, the salt crystallization process, salt harvesting and drying. The results obtained from this activity are that the salt product produced using SHE technology has better quality compared to ponds that use soil as a crystallization table. In addition, the amount of salt produced has increased by around 300%. Salt production can be carried out throughout the season or does not affect the weather. Besides that, the salt products produced are more hygienic because they are protected from pollution.